ANALISIS DEBIT RANCANGAN MENGGUNAKAN METODE HASPERS PADA DAS BABAK KABUPATEN LOMBOK TENGAH: Design Discharge Analysis Using The Haspers Method In The Babak District Of Central Lombok District - Wicaksana, I Gede Arya; Yamin, Muhamad; Aminullah, Aminullah; Dharma S., Bagus Widhi; Ahadi, Giatma Dwijuna; Winardi, Agus (Yayasan Al-Amin Qalbu, 2025)
The Babak River Watershed is located in Tanah Beak Village and borders directly with Bagu Village, Pringgarata District, Central Lombok Regency, which is one of the areas where river flooding and drainage systems often occur. In the analysis, the method used is to collect rainfall data and river watershed (DAS) data, the data is analyzed using the Normal method, Normal log, Person Type III log and Gumbel method, then calculate the design discharge PMP value, after the calculation is carried out, the discharge is obtained. design in the Babak river basin using the Haspers method for each 2 year return period the discharge is = 55966.851 m3/sec, 5 year return period the discharge is = 58655.999 m3/sec, 10 year return period the discharge is = 60437 .904 m3/sec, 20 year return period debit of = 62125.576 m3/sec, 25 year return period debit of = 62687.966 m3/sec, 50 year return period debit of = 64356.591 m3/sec, return period 100 years of discharge is = 66027.221 m3/sec. Meanwhile, the maximum rainfall value that may occur, the PMP value is obtained = 967.256 mm.